2011
DOI: 10.1007/s10646-011-0797-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute exposure to exogenous ammonia on cerebral monoaminergic neurotransmitters in juvenile Solea senegalensis

Abstract: The present study explored the potential role of brain catecholaminergic and serotoninergic systems as neuronal targets for the toxicological effects of acute ammonia exposure (0.28 mg l(-1) of un-ionized ammonia for 12 and 24 h) in juvenile sole (Solea senegalensis). In addition, plasma cortisol levels were measured. The results showed significant increases in their concentrations that were similar after 12 and 24 h of exposure. These data indicate that acute exposure (12 and 24 h) to ammonia initiates a typi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 60 publications
1
18
0
Order By: Relevance
“…The initial activation of the brain monoaminergic neurons could be part of the stressor recognition mechanisms, taking part in the central integration of the stress signals to initiate the neuroendocrine response. The observed peaks in both hypothalamic and telencephalic serotonergic activities 45 min after stress could be the result of the indirect effects of other participants in the stress response such as cortisol, which is known to promote serotonergic activity in fish (Summers and Winberg, 2006;Weber et al, 2012). It is known that the regulation of the serotonergic neuronal system is different in cases of chronic stress, where the activation seems to be more permanent (Øverli et al, 2005; Øverli et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial activation of the brain monoaminergic neurons could be part of the stressor recognition mechanisms, taking part in the central integration of the stress signals to initiate the neuroendocrine response. The observed peaks in both hypothalamic and telencephalic serotonergic activities 45 min after stress could be the result of the indirect effects of other participants in the stress response such as cortisol, which is known to promote serotonergic activity in fish (Summers and Winberg, 2006;Weber et al, 2012). It is known that the regulation of the serotonergic neuronal system is different in cases of chronic stress, where the activation seems to be more permanent (Øverli et al, 2005; Øverli et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, both stimulatory and inhibitory effects of stress on dopaminergic activity have been reported (Höglund et al, 2001;Waters et al, 2005). In fish, although several studies have reported a stimulatory action of different kinds of stressors on the central dopaminergic system (Backström et al, 2011;Gesto et al, 2008;Øverli et al, 1999;Weber et al, 2012), such stimulation did not always take place (M.G. and J.M.M., unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the numerous studies that have addressed the effect of stress factors on serotoninergic and catecholaminergic systems in mammals, relatively few such studies have been carried out with fishes, and most of the existing studies have focused on the effect of social stress or stress associated with exposure to toxic chemicals. Thus, increased brain serotoninergic and dopaminergic activity have been observed in salmonids subjected to social stress (Winberg & Nilsson, ; Winberg & Lepage, ; Øverli et al , ; Cubitt et al , ) and in salmonids and Senegalese sole Solea senegalensis (Kaup 1858) subjected to stress induced by exposure to toxic chemicals (Gesto et al , ; Weber et al , ). A recent study has also shown that acute handling stress induces a rapid increase in serotoninergic and dopaminergic activity in the telencephalon of rainbow trout Oncorhynchus mykiss (Walbaum 1792) (Gesto et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Ammonia and nitrite are toxic to fish. [11][12][13][14][15][16][17][18][19][20] Weber et al [21] discovered that the brain dopaminergic and serotonergic systems are neuronal targets for the toxicological effects of acute ammonia exposure. Miron et al [22] found that exposure to ammonia increased the total ammonia levels in tissues and damaged the gill epithelium in juvenile silver catfish, Rhamdia quelen (Heptapteridae).…”
Section: Introductionmentioning
confidence: 99%